Posthuman Readings of The Last Unicorn: Myth Resignification and Feminine Subjectivity - Rivera Calderón, Paula (2026)
This article analyzes The Last Unicorn (1982) as a contemporary rereading of the unicorn myth from a posthuman feminist and ecofeminist perspective. Drawing on the historical and cultural context of the unicorn figure, it examines how the film resignifies attributes traditionally associated with femininity. The film enables a critical interrogation of the dichotomies between human and nonhuman, nature and culture, reality and fantasy, as well as the ways these oppositions have historically shaped the construction of femininity. It concludes that the resignification of the unicorn myth does not merely revisit a traditional symbolic figure, but rather opens up alternative imaginaries of subjectivity and existence, with a transformative potential that articulates the personal, the political, and the ethical.